Autoinducer-2 Quorum Sensing Contributes to Regulation of Microcin PDI in Escherichia coli - Lu, Shao-Yeh; Zhao, Zhe; Avillan, Johannetsy J.; Liu, Jinxin; Call, Douglas R. (Frontiers in Microbiology, 2017)
The Escherichia coli quorum sensing (QS) signal molecule, autoinducer-2 (AI-2), reaches its maximum concentration during mid-to-late growth phase after which it quickly degrades during stationary phase. This pattern of AI-2 concentration coincides with the up- then down-regulation of a recently described microcin PDI (mccPDI) effector protein (McpM). To determine if there is a functional relationship between these systems, a prototypical mccPDI-expressing strain of E. coli 25 was used to generate ∆luxS, ∆lsrACDBFG (∆lsr), and ∆lsrR mutant strains that are deficient in AI-2 production, transportation, and AI-2 transport regulation, respectively. Trans-complementation, RT-qPCR, and western blot assays were used to detect changes of microcin expression and synthesis under co-culture and monoculture conditions. Compared to the wild-type strain, the AI-2-deficient strain (∆luxS) and -uptake negative strain (∆lsr) were >1000-fold less inhibitory to susceptible bacteria (P < 0.05). With in trans complementation of luxS, the AI-2 deficient mutant reduced the susceptible E. coli population by 4-log, which was within 1-log of the wild-type phenotype. RT-qPCR and western blot results for the AI-2 deficient E. coli 25 showed a 5-fold reduction in mcpM transcription with an average 2-h delay in McpM synthesis. Furthermore, overexpression of sRNA micC and micF (both involved in porin protein regulation) was correlated with mcpM regulation, consistent with a possible link between QS and mcpM regulation. This is the direct first evidence that microcin regulation can be linked to quorum sensing in a Gram-negative bacterium.